Mortality and Cardiovascular Events Are Best Predicted by Low Central/Peripheral Pulse Pressure Amplification But Not by High Blood Pressure Levels in Elderly Nursing Home Subjects: The PARTAGE (Predictive Values of Blood Pressure and Arterial Stiffness in Institutionalized Very Aged Population) Study - BENETOS, Athanase; GAUTIER, Sylvie; MANCKOUNDIA, Patrick; ROLLAND, Yves; HANON, Olivier; PERRET-GUILLAUME, Christine; LACOLLEY, Patrick; SAFAR, Michel E; GUILLEMIN, Francis; LABAT, Carlos; SALVI, Paolo; VALBUSA, Filippo; et al. (Journal of the American College of Cardiology, 2012)
The aim of the longitudinal PARTAGE study was to determine the predictive value of blood pressure (BP) and pulse pressure amplification, a marker of arterial function, for overall mortality (primary endpoint) and major cardiovascular (CV) events, in subjects older than 80 years of age living in a nursing home. Assessment of pulse indexes may be important in the evaluation of the CV risk in very elderly frail subjects. A total of 1,126 subjects (874 women) who were living in French and Italian nursing homes were enrolled (mean age, 88 ± 5 years). Central (carotid) to peripheral (brachial) pulse pressure amplification (PPA) was calculated with the help of an arterial tonometer. Clinical and 3-day self-measurements of BP were conducted. During the 2-year follow-up, 247 subjects died, and 228 experienced major CV events. The PPA was a predictor of total mortality and major CV events in this population. A 10% increase in PPA was associated with a 24% (p < 0.0003) decrease in total mortality and a 17% (p < 0.01) decrease in major CV events. Systolic BP, diastolic BP, or pulse pressure were either not associated or inversely correlated with total mortality and major CV events. In very elderly individuals living in nursing homes, low PPA from central to peripheral arteries strongly predicts mortality and adverse effects. Assessment of this parameter could help in risk estimation and improve diagnostic and therapeutic strategies in very old, polymedicated persons. In contrast, high BP is not associated with higher risk of mortality or major CV events in this population. (Predictive Values of Blood Pressure and Arterial Stiffness in Institutionalized Very Aged Population [PARTAGE]; NCT00901355).